2012
DOI: 10.1002/hep.25536
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of curative treatment for hepatocellular cancer in nonalcoholic steatohepatitis versus hepatitis C and alcoholic liver disease

Abstract: Concomitant increasing incidences of hepatocellular carcinoma (HCC) and nonalcoholic steatohepatitis (NASH) suggest that a substantial proportion of HCC arises as a result of hepatocellular injury from NASH. The aim of this study was to determine differences in severity of liver dysfunction at HCC diagnosis and long-term survival outcomes between patients undergoing curative therapy for HCC in the background of NASH compared to hepatitis C virus (HCV) and/or alcoholic liver disease (ALD). Patient demographics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
166
6
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(200 citation statements)
references
References 54 publications
21
166
6
4
Order By: Relevance
“…In a study from Germany, only 58 % of 36 NAFLD-related HCC had cirrhosis at time of HCC diagnosis [33]. A single-center study among HCC patients undergoing curative resection evaluated explant specimens and found significantly lower prevalence of cirrhosis among NASH-HCC than HCV-or alcohol-related HCC (73 vs. 94 %) [42]. We conducted a study using a national cohort of 1500 veterans diagnosed with HCC and found that 35 % of NAFL D-related HCC and 19 % of HCC with metabolic syndrome did not have evidence of cirrhosis at the time of HCC diagnosis compared with 10 % of those with alcohol abuse or HCV-related HCC [76].…”
Section: Hcc In Absence Of Cirrhosismentioning
confidence: 97%
See 1 more Smart Citation
“…In a study from Germany, only 58 % of 36 NAFLD-related HCC had cirrhosis at time of HCC diagnosis [33]. A single-center study among HCC patients undergoing curative resection evaluated explant specimens and found significantly lower prevalence of cirrhosis among NASH-HCC than HCV-or alcohol-related HCC (73 vs. 94 %) [42]. We conducted a study using a national cohort of 1500 veterans diagnosed with HCC and found that 35 % of NAFL D-related HCC and 19 % of HCC with metabolic syndrome did not have evidence of cirrhosis at the time of HCC diagnosis compared with 10 % of those with alcohol abuse or HCV-related HCC [76].…”
Section: Hcc In Absence Of Cirrhosismentioning
confidence: 97%
“…Another limitation is the potential for reverse causality, by which some of the risk factors (e.g., diabetes or BMI) are affected by the development of HCC or the preceding cirrhosis. Our search found at least 9 studies performed in Asia (n=7 in Japan), 6 in Europe, and 7 in the USA [8,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]44•, 45•] (Table 1C). All compared a case group with HCC attributed to NASH/NAFLD or to CC presumptively NAFLD related, with at least 1 control group, typically with HCC attributed to another cause of liver disease (n=19); though 2 had only NASHrelated cirrhosis controls without HCC as their sole comparison or control group.…”
Section: Case-control and Cross-sectional Studiesmentioning
confidence: 99%
“…A similar mix of therapies was seen in the comparison group of 162 patients, with 51% undergoing liver transplantation, 32% surgical resection and 20% ablation. Three-year overall survival was significantly better in the NASH group (60.9%) than in the HCV-alcohol group (36.2%), with no difference in recurrence-free survival (60 vs. 50 months, median survival) [20]. Given similar tumor characteristics and recurrence-free survival rates, overall survival is most likely predicated not by tumor presentation but by the poorer liver function associated with the HCV-alcohol group.…”
Section: Treatment Of Nash-related Cirrhosis and Hccmentioning
confidence: 99%
“…Currently, there are no published series examining the outcome of either locoregional therapies, including transarterial chemoembolization and Yttrium-90 therapy, or systemic therapies. Reddy et al [20] have recently published the largest series of patients with NASH-related HCC who have undergone curative-intent therapy (surgical resection, liver transplantation or tumor ablation). They compared outcomes to a cohort of patients with HCV- or alcohol-related HCC who were presented over the same 11-year time period.…”
Section: Treatment Of Nash-related Cirrhosis and Hccmentioning
confidence: 99%
See 1 more Smart Citation